2015
DOI: 10.1136/postgradmedj-2015-133496
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes in patients with Acute Kidney Injury: the impact of hospital based automated AKI alerts

Abstract: BackgroundAcute kidney injury (AKI) is a significant cause of morbidity and mortality. Early identification may improve the outcome and in 2012 our hospital introduced an automated AKI alert system for early detection and management of AKI.ObjectivesUsing an automated AKI alert system we analysed whether early review and intervention by the Critical Care and Outreach (CCOT) team improved patient outcomes in AKI and whether serum bicarbonate was useful in predicting outcomes in patients with AKI.MethodsIn a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Although most vancomycin nephrotoxic events are deemed reversible, available data support there is prolonged hospitalization, increased mortality rate and higher incidence of ESKD from AKI of any cause [Prendecki et al 2016]. For this reason, awareness of these complications particularly in critically ill patients may allow prompt intervention.…”
Section: Prevention Of Vancomycin-induced Akimentioning
confidence: 99%
“…Although most vancomycin nephrotoxic events are deemed reversible, available data support there is prolonged hospitalization, increased mortality rate and higher incidence of ESKD from AKI of any cause [Prendecki et al 2016]. For this reason, awareness of these complications particularly in critically ill patients may allow prompt intervention.…”
Section: Prevention Of Vancomycin-induced Akimentioning
confidence: 99%
“…Acute kidney injury (AKI) is one of the most common complications in hospitalized patients and shows a rapidly increasing incidenceespecially in the elderly 1,2 . Although partial recovery occurs in the majority of patients, AKI is strongly associated with prolonged hospitalization, increase of mortality and progression to end-stage renal disease (ESRD) [3][4][5][6][7] . ESRD can also be the consequence of recurrent, minor episodes of AKI during lifetime 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This study showed a convincing sevenfold decrease in the requirement of renal replacement therapy and a 2.4fold decrease in mortality in patients receiving supportive therapy on the day of the alert compared to patients receiving delayed supportive therapy (day 1 or later). 22 Of note, this intervention was based on the review of serial creatinine measurements, and the additional 24-hour window of opportunity provided delta PENK could potentially provide even bigger benefits. 23 Potential limitations of the current study merit consideration.…”
Section: Discussionmentioning
confidence: 99%